2017
DOI: 10.1016/j.scitotenv.2017.03.276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the synoptic winter mortality climatology in five regions of England: Searching for evidence of weather signals

Abstract: Although heat-related mortality has received considerable research attention, the impact of cold weather on public health is less well-developed, probably due to the fact that physiological responses to cold weather can vary substantially among individuals, age groups, diseases etc., depending on a number of behavioral and physiological factors. In the current work we use the classification techniques provided by the COST-733 software to link synoptic circulation patterns with excess cold-related mortality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Nutritional factors include major and trace dietary elements, vitamins, unsaturated fatty acids, and so forth. In the elderly, extreme temperatures have a significant impact on mortality [ 1 , 2 , 3 , 4 , 5 , 6 ], and exposure, or lack of exposure, to the climatic change often prompts long-term effects of harsh winters can contribute to differences in mortality among these individuals [ 7 ]. Hypoxia induced by living at higher altitudes affects health and disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional factors include major and trace dietary elements, vitamins, unsaturated fatty acids, and so forth. In the elderly, extreme temperatures have a significant impact on mortality [ 1 , 2 , 3 , 4 , 5 , 6 ], and exposure, or lack of exposure, to the climatic change often prompts long-term effects of harsh winters can contribute to differences in mortality among these individuals [ 7 ]. Hypoxia induced by living at higher altitudes affects health and disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lupo et al (2014) correlated hot, dry summers in Moscow, Russia, like the fatal summer of 2010, with atmospheric blocking and El Niño transitions. In the case of England, winter mortality has been associated with cold air masses originating from continental Europe or with eastern flows resulting in rapid changes in weather conditions (Paschalidou et al, 2017). Additionally, a west-to-east contrast in the nature of air masses linked with increased mortality was identified by Dimitriou et al (2016) who reported that, for the West Midlands and northwest regions of England, relatively warm weather conditions from the west are associated with the highest daily average winter mortality, whereas, for the northeast, Humberside/York, and the southeast regions, cold continental air advection from northern/eastern Europe appears to be important in mortality terms.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is largest between 3 and 5 weeks after the SSW central date and results in 621 (95% empirical confidence interval [eCI] = 84, 1,136) additional deaths or a 1.7 (eCI = 0.4, 3.1) percentage point increase above median mortality. This work adds to a growing literature assessing the influence of atmospheric flow types on mortality (Paschalidou et al, 2017;Charlton-Perez et al, 2019;Psistaki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%